Pengaruh Pengetahuan Kewirausahaan, Lingkungan Keluarga, Dan Motivasi Terhadap Minat Berwirausahaan (Studi Pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Islam Malang) - Fandy Armanto; Jeni Susyanti; Etty Saraswati (UNIVERSITAS ISLAM MALANG, 2021)
Abstract The purpose of this study was to explain entrepreneurial knowledge, family environment, motivation, and interest in entrepreneurship and to find out partially explain entrepreneurial knowledge, family environment, and motivation to interest in entrepreneurship. This research method uses quantitative methods and this type of research is probability sampling using purposive sampling technique. The sample of this study was 83 FEB students class 2017 at the Islamic University of Malang. To obtain accurate and detailed data, this study used a questionnaire data collection method. The data analysis used is descriptive analysis, instrument test, normality test, classical assumption, multiple linear regression analysis, hypothesis testing, and coefficient of determination using SPSS 25 for Windows. The results of this study indicate that entrepreneurial knowledge, family environment, and motivation affect the interest in entrepreneurship in students of the 2017 Faculty of Economics and Business at the Islamic University of Malang. Keywords: entrepreneurship knowledge, family environment, motivation, dan interest in entrepreneurship.